First case of a dog bite wound infection caused by Streptococcus minor in human. (November 2016) - Tré-Hardy, M.; Saussez, T.; Yombi, J.C.; Rodriguez-Villalobos, H.
Abstract: We report the first case of human infection caused by Streptococcus minor in a 51-year-old immunocompetent woman admitted for dog bite injuries. At present, the role of Streptococcus minor in bite wound infections is unknown. Further studies on virulence factors are needed to elucidate its pathogenicity mechanisms.